Analysis of the Effects of Different Driving Cycles on the Driving Range and Energy Consumption of BEVs - Rubao Cheng; Wei Zhang; Jue Yang; Sun Wang; Laiao Li (World Electric Vehicle Journal)
BEVs (Battery Electric Vehicles) have received widespread attention from various countries for their potential in combating global warming, the energy crisis, and environmental pollution. The driving range and energy consumption of BEVs vary significantly under different driving cycles, which often results in discrepancies between the values reported by manufacturers and real-world data. To address this issue, this paper establishes a modular simulation model of a BEV on the Matlab/Simulink platform and conducts simulation experiments and analyses of driving range and energy consumption under three different standard driving cycles, namely, the NEDC (New European Driving Cycle), WLTC (World Light Vehicle Test Cycle), and CLTC-P (China Light-duty Vehicle Test Cycle for Passenger Car), and compares the results with data from vehicle manufacturers and consumers. The results of the study show that the NEDC conditions are more ideal, the CLTC-P conditions are the most intense vehicle driving, and the WLTC conditions require the highest overall vehicle performance. Compared with other standard cycles, the WLTC conditions show better alignment with real-world driving range data. The two main factors affecting the energy consumption in each condition are driving range and acceleration. The energy recovery strategy, braking frequency, and average deceleration speed of the driving cycle conditions are important factors affecting the braking energy recovery. This study provides a theoretical basis for driving range and energy consumption testing and driving cycle condition improvement of BEVs.